2018
DOI: 10.1371/journal.pone.0198891
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome profiling of Blumeria graminis f. sp. tritici during compatible and incompatible interactions with sister wheat lines carrying and lacking Pm40

Abstract: Blumeria graminis f. sp. tritici (Bgt) is an obligate biotrophic fungus that causes wheat powdery mildew, which is a devastating disease in wheat. However, little is known about the pathogenesis of this fungus, and differences in the pathogenesis of the same pathogen at various resistance levels in hosts have not been determined. In the present study, leaf tissues of both Pm40-expressing hexaploid wheat line L658 and its Pm40-deficient sister line L958 were harvested at 0 (without inoculation), 6, 12, 24, 48 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…This flexibility may be facilitated by the fact that pathogenesis does not involve the formation of complex penetration or feeding structures that require fine‐tuned developmental programs. In powdery mildew which need to form appressoria as well as haustoria to establish host infections, comparative transcriptomics during early pathogenesis identified a comparatively low number of isolate‐specifically expressed genes in two barley powdery mildew strains (Hacquard et al, ) and showed that transcriptional programs are similar even during incompatible infections and interactions with nonhost species (Hacquard et al, ; Hu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This flexibility may be facilitated by the fact that pathogenesis does not involve the formation of complex penetration or feeding structures that require fine‐tuned developmental programs. In powdery mildew which need to form appressoria as well as haustoria to establish host infections, comparative transcriptomics during early pathogenesis identified a comparatively low number of isolate‐specifically expressed genes in two barley powdery mildew strains (Hacquard et al, ) and showed that transcriptional programs are similar even during incompatible infections and interactions with nonhost species (Hacquard et al, ; Hu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, differences in the infection mechanism of Bgt during the interactions with L658 and L958 were determined [ 54 ]. To further clarify the difference in the molecular response mechanisms between L658 and L958, we continued to analyse the RNA-seq data from the plant side.…”
Section: Resultsmentioning
confidence: 99%
“…The resistant wheat line L658 carrying Pm40 and its susceptible sister line L958 without Pm40 were used for comparative analyses by observations of cytological changes and determinations of physiological and biochemical indices. In addition, RNA-seq was performed for wheat plants after they were inoculated with Bgt , as described previously [ 54 ]. The fungus was a single-spore isolate collected from a field at Wenjiang Farm, Chengdu, Sichuan Province, and propagated weekly on the highly susceptible wheat line CY20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Blumeria graminis f. sp. Tritici (Bgt strain E09) was maintained on susceptible wheat 'MingXian 169' [77]. The 7-day-old seedlings were inoculated with Bgt conidia from 'MingXian 169' seedlings infected 10 days previously.…”
Section: Cis-elements Analysis and Expression Pattern Analysementioning
confidence: 99%